Preparation and Loading Process of Single Crystalline Samples into a Gas Environmental Cell Holder for In Situ Atomic Resolution Scanning Transmission Electron Microscopic Observation. (30th March 2016) - Straubinger, Rainer; Beyer, Andreas; Volz, Kerstin
Abstract: A reproducible way to transfer a single crystalline sample into a gas environmental cell holder for in situ transmission electron microscopic (TEM) analysis is shown in this study. As in situ holders have only single-tilt capability, it is necessary to prepare the sample precisely along a specific zone axis. This can be achieved by a very accurate focused ion beam lift-out preparation. We show a step-by-step procedure to prepare the sample and transfer it into the gas environmental cell. The sample material is a GaP/Ga(NAsP)/GaP multi-quantum well structure on Si. Scanning TEM observations prove that it is possible to achieve atomic resolution at very high temperatures in a nitrogen environment of 100, 000 Pa.